PENGARUH FINANCIAL DISTRESS, AUDIT TENURE, DAN UMUR PERUSAHAAN TERHADAP KETEPATAN WAKTU PUBLIKASI LAPORAN KEUANGAN AUDITAN - Trisnadevy, Dini Mauli; Satyawan, Made Dudy (Jurnal Akuntansi AKUNESA, 2020)
This study aims to examine the effect of financial distress, audit tenure, and age of the company on timeliness publication of audited financial statement. The sample in this study were mining companies from the BEI for the periode 2014-2017. The sample were selected using purposive sampling technique and obtained a sample of 35 companies. The analysis technique used in this study is logistic regression analysis using IBM SPSS Statistic program 23. The result of the study show that audit tenure has a negative effect on timeliness. While other variables such as audit tenure and age of the company showed no effect on timeliness.